Upton Sinclair´s Novel in Czech Translations - Vyhnálková, Petra (Univerzita Pardubice, 2013)
This bachelor paper deals with the novel by Upton Sinclair - The Jungle and its two Czech alterations. The first part of the thesis concentrates on the characteristics of the famous American author together with the presentation of the context with respect of American literature. After, the synopsis of the novel is introduced including its then comments. The rest of the theoretical part is associated with theoretical approaches to translating and the two Czech translators are mentioned there as well. The last chapter explains chosen terms from the field of linguistics which are included within the practical part. The analysis is based on the comparison of the two Czech versions of the novel where the aforementioned terms concerning syntax and lexicology are to be commented on. The final part represents a Conclusion which summarizes entire findings and features of both the Czech alterations with regard to the period of time.
Román Uptona Sinclaira v českých překladech
Keywords: Amerika; Sinclair, Upton; naturalismus; překlady; komparace; analýzy; America; Naturalism; translation; comparison; analysis